Characteristics of flow field in 100 t dephosphorization ladle furnace with top lance - LIU Fu-hai; ZHU Rong; WANG Qi-gang; BAI Rui-guo (工程科学学报)
Characteristics of flow field and stirring effects of top lance with various tilt angles(Tilt angles were 39°,41°,43°,45° and 47°,respectively) on the molten bath were studied using water experiment and Fluent software. It was found that appropriate tilt angle could improve dephosphorization process,and too large and too small reduced the impacting depth and impacting diameter,respectively,leading to decrease in dephosphorization rate. When injecting by the 43° oxygen lance,impacting depth and impacting diameter were medium,mixing time and volume of dead-zone were the minimum and average flow velocity of molten bath was the biggest. This is helpful to promote phosphorus dispersion in dephosphorization ladle furnace and improve the dephosphorization rate.Based on the results of industrial application research,the 43° oxygen lance could stir the molten bath better,increase the dephosphorization rate and reduce the consumption of hot metal and scrap.